Debt relief for poor countries - Addison, Tony.; Hansen, Henrik, 1962-; Tarp, Finn, 1951-; World Institute for Development Economics Research (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2004)
This book is an outcome of a UNU-WIDER conference held in Helsinki in August 2001- offers a variety of perspectives on the economics of HIPS.
This book is an outcome of a UNU-WIDER conference held in Helsinki, in August 2001.
Includes bibliographical references and index.
aia 2/05/13
Loan
Keywords: Debt relief -- Developing countries; Debts, External -- Developing countries